The Transformative Influence of Artificial Intelligence in 2024: Innovations, Impacts, and Challenges - Gerel Goryanova (Scientific Research and Experimental Development, 2024)
The year 2024 marks a transformative phase in the evolution of Artificial Intelligence (AI). This technology has revolutionized industries such as healthcare, education, and environmental management, demonstrating unparalleled potential to address global challenges. However, these advancements bring ethical concerns, governance issues, and societal disruptions that require urgent attention. This paper explores the technological innovations driving AI's development, its profound societal impacts, and the challenges it faces in implementation and regulation. Through in-depth analyses and case studies, the article highlights both the promise and perils of AI. It calls for inclusive policymaking, ethical frameworks, and international collaboration to harness AI’s transformative potential responsibly and equitably.